Differential equations demystified - Krantz, Steven G. 1951- 4 0 (Steven George),16; 5 (New York : McGraw-Hill, 2005)
A step-by-step self-teaching guide to differential equations featuring worked examples, You Try It exercises, end-of-chapter problems, and a 100-question final exam.
Includes bibliographical references (p. 317-318) and index.
Choice
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Differential equations.;Differential equations; 20; 2